Retail management: Satisfaction of consumer needs - Marquardt, Raymond A (Dryen Press, 1975)
This book presents a discussion of the process of the continuous chice of appropriate alternatives. It provides the reader with more than a descriptive view of retailing by using marketing analysis to obtain the "why" and "how," in addition to the "what," of retailing.